A Novel 19$\sqrt {19} $ × 19$\sqrt {19} $ Superstructure in Epitaxially Grown 1T‐TaTe2. Issue 38 (20th August 2022) - Hwang, Jinwoong; Jin, Yeongrok; Zhang, Canxun; Zhu, Tiancong; Kim, Kyoo; Zhong, Yong; Lee, Ji‐Eun; Shen, Zongqi; Chen, Yi; Ruan, Wei; Ryu, Hyejin; Hwang, Choongyu; et al.
Abstract: The spontaneous formation of electronic orders is a crucial element for understanding complex quantum states and engineering heterostructures in 2D materials. A novel 19 $\sqrt {19} $ × 19 $\sqrt {19} $ charge order in few‐layer‐thick 1T‐TaTe2 transition metal dichalcogenide films grown by molecular beam epitaxy, which has not been realized, is report. The photoemission and scanning probe measurements demonstrate that monolayer 1T‐TaTe2 exhibits a variety of metastable charge density wave orders, including the 19 $\sqrt {19} $ × 19 $\sqrt {19} $ superstructure, which can be selectively stabilized by controlling the post‐growth annealing temperature. Moreover, it is found that only the 19 $\sqrt {19} $ × 19 $\sqrt {19} $ order persists in 1T‐TaTe2 films thicker than a monolayer, up to 8 layers. The findings identify the previously unrealized novel electronic order in a much‐studied transition metal dichalcogenide and provide a viable route to control it within the epitaxial growth process. Abstract : A novel 19 × 19 $\sqrt {19} × \sqrt {19} $ charge order is observed in few‐layer thick 1T‐TaTe2 films grown by molecular beam epitaxy. The photoemission and scanning probe measurements demonstrate that monolayer 1T‐TaTe2 exhibits various metastable charge density wave orders, including the 19 × 19 $\sqrt {19} × \sqrt {19} $ superstructure, which can be selectively stabilized by postgrowth annealing. In 1T‐TaTe2 films thicker than a monolayer, only the 19 × 19 $\sqrt {19} × \sqrt {19} $ order persists.